Evaluation of Hypoglycaemic Effects of Dipeptidyl Peptidase–4 Inhibitors and Biguanide on Type-2 Diabetic subjects: A six months trial - Naghma , Sadia M Azam Khan , Atta Ullah Khan , Zahoor Ahmed , Mohammad Umar, Muhammad Shabbir Khan , Mohammad Tayyab Ahmad , Naghma , Sadia M Azam Khan , Atta Ullah Khan , Zahoor Ahmed , Mohammad Umar, Muhammad Shabbir Khan , Mohammad Tayyab Ahmad (Journal of Rawalpindi Medical College, 2020)
Objective: This trial was conducted to evaluate the effectiveness of oral hypoglycemic agents on diabetic control and biochemical parameters of known diabetic subjects. Introduction: T2DM occurs due to abnormal metabolism of carbohydrate, proteins and lipids leading to increased blood glucose characterized by polyuria and polydypsia due to relative 5deficiency or lack of insulin. Beside dietary control and insulin therapy, various oral hypoglycemic such as sulfonylurea biguanide, thiazolidinedione, DPP–4 inhibitors, glucagon–like peptide inhibitors and SGL2. Material and Methods: This comparative trial was carried out on previously diagnosed type–2 diabetic subjects. This trial was conducted at health care centers of District Nowshehra viz. NMC Nowshehra, DHQ Hospital Nowshehra, and ICS, Peshawar in collaboration with KMC and PIMC Peshawar, Khyber Pakhtunkhwa, Pakistan. A total of 200 known diabetic subjects were randomly recruited on the basis of predetermined selection criteria and were splited into two groups. Group A having 100 diabetic subjects was given DPP–4 inhibitor; Sitagliptin 50 mg two times a day alone for six (06) months while Group B comprising of 100 patients were treated with combination of DPP–4 inhibitor (Sitagliptin 50 mg 1BD) and Metformin in a dose of 500 mg two times a day. Venous blood samples were taken from each patient in both fasting (10–12 hour night long fast) and random (2 hour post prandial) state. FBS, RBS, HbA1C, S. creatinine and fasting S. lipid profile were determined by using spectrophotometric colorimetric methods using kits (procured from Elitech, Spain) at 03 and 06 months follow up. Inclusion criteria was subjects with T2DM of age 18 years and above. T2DM patients on insulin, diabetic nephropathy and retinopathy were excluded. The data was analyzed by using SPSS software version 20. Results: Significant results (p < 0.05) were seen for glycemic control (FBS, RBS, HbA1C) in Group B as compare to Group A patients.